Whole-Brain Monosynaptic Afferents to Rostromedial Tegmental Nucleus Gamma-Aminobutyric Acid-Releasing Neurons in Mice - Zhao, Ya-Nan; Zhang, Yang; Tao, Shi-Yuan; Huang, Zhi-Li; Qu, Wei-Min; Yang, Su-Rong (Frontiers in Neuroscience, 2022)
Increasing evidence has revealed that the rostromedial tegmental area (RMTg) mediates many behaviors, including sleep and addiction. However, presynaptic patterns governing the activity of γ-aminobutyric acid-releasing (GABAergic) neurons, the main neuronal type in the RMTg, have not been defined. Here, we used cell-type-specific retrograde trans-synaptic rabies viruses to map and quantify the monosynaptic afferents to RMTg GABAergic neurons in mouse whole brains. We identified 71 ascending projection brain regions. Sixty-eight percent of the input neurons arise from the ipsilateral and 32% from the contralateral areas of the brain. The first three strongest projection regions were the ipsilateral lateral hypothalamus, zone incerta, and contralateral pontine reticular nucleus. Immunohistochemistry imaging showed that the input neurons in the dorsal raphe, laterodorsal tegmentum, and dorsal part of zone incerta were colocalized with serotoninergic, cholinergic, and neuronal nitric oxide synthetase-expressing neurons, respectively. However, in the lateral hypothalamus, a few input neurons innervating RMTg GABAergic neurons colocalized orexinergic neurons but lacked colocalization of melanin-concentrating hormone neurons. Our findings provide anatomical evidence to understand how RMTg GABAergic neurons integrate diverse information to exert varied functions.